#### Answer

$=\frac{2}{7}$

#### Work Step by Step

Applying power rules:
$\frac{(3a^2)^3(2b^{-1})^2}{(7a^3)^2(3b^{2})^{-1}}$
$=\frac{3a^62b^{-2}}{7a^63b^{-2}}$
$=\frac{3.2}{7.3}$
$=\frac{2}{7}$

Chegg costs money, GradeSaver solutions are free!

Published by
Prentice Hall

ISBN 10:
0133281140

ISBN 13:
978-0-13328-114-9

$=\frac{2}{7}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.